Characteristics of air quality in Tianjin during the Spring Festival period of 2015. Issue 1 (2nd January 2016) - Tang, Miao; Ji, Dong-Sheng; Gao, Wen-Kang; Yu, Zhong-Wang; Chen, Kui; Cao, Wan
Abstract: To better understand the characteristics of air quality and the relationship between the chemical composition evolution and source variation, an intensive atmospheric campaign was conducted in Tianjin, a megacity of the North China Plain, from 10 February to 6 March 2015. There were 20 days exceeding the threshold value of secondary Chinese Ambient Air Quality Standards for PM2.5 (75 μg m −3, daily average over 24 h) during the study period. Five air pollution episodes were selected for investigation. During the pre-holiday pollution episode, NH4 +, NO3 −, and SO4 2− were more abundant, indicating that air pollution was caused by motor vehicle exhaust emissions and coal consumption under unfavorable meteorological conditions. During Chinese Lunar New Year's Eve, widespread use of fireworks resulted in extremely high aerosol concentrations. Firework displays caused increases in K + and also enrichment of SO4 2− relative to NO3 − . The holiday pollution episode was caused by regional transport, characterized by abundant SO4 2− and NH4 + . In addition, the aging processes of the particles from fireworks discharge played an important role in the formation of NO3 − and SO4 2− . The Lantern Festival episode was characterized by a transition from the enrichment of K + to secondary inorganic ions (NO3 −, SO4 2−, and NH4 + ). The results of this study are useful for a detailed understanding of the variation in atmospheric compositions and sources caused by anthropogenic activity, and highlight the importance of controlling intensive fireworks discharge.